Genomic surveillance during the first two years of the COVID-19 pandemic – country experience and lessons learned from Türkiye - Yalçın, Süleyman; Coşgun, Yasemin; Dedeoğlu, Ege; Kopp, Katharina; Bayrakdar, Fatma; Ünal, Gültekin; Musul, Biran; Sağtaş, Ekrem; Korukluoğlu, Gülay; Raftery, Philomena; Kaygusuz, Sedat (Frontiers in Public Health, 2024)
Türkiye confirmed its first case of SARS-CoV-2 on March 11, 2020, coinciding with declaration of the global COVID-19 pandemic. Türkiye swiftly increased testing capacity and implemented genomic sequencing in 2020, producing 80,000 sequences by February 2022. This paper describes Türkiye's journey of establishing genomic surveillance as a middle-income country with limited prior sequencing capacity and analyses 14 months of sequencing data. We highlight the challenges experienced and globally relevant lessons.We track the evolution of the COVID-19 pandemic in Türkiye from December 2020 to February 2022 through a timeline and present epidemiological, vaccination and testing data. To investigate the phylodynamics and phylogeographics of SARS-CoV-2, we used Nextstrain to analyse 31,629 highquality genomes sampled from seven regions around Türkiye.Türkiye's epidemiological curve, mirroring global trends, featured four distinct waves, each coinciding with the emergence and spread of variants of concern (VOCs). Utilizing locally manufactured kits to expand testing capacity and introducing variant-specific RT-qPCR tests developed in partnership with a private company was a strategic advantage in Türkiye given the scarcity and fragmented global supply chain early in the pandemic. Türkiye contributed almost 80,000 genomic sequences to global databases by February 2022, ensuring data had a global impact. The synergy of variant-specific RT-qPCR kits and genomic sequencing enabled cost-effectively monitoring of VOCs, however, data analysis was constrained by a weak sequencing sampling strategy and fragmented data management systems, limiting the impact on public health response. Phylodynamic analysis indicated that Türkiye's geographical position as an international travel hub influenced both national and global transmission of each VOC, despite travel restrictions.This paper provides valuable insights into the testing and genomic surveillance systems adopted by Turkiye during the COVID-19 pandemic, proposing important lessons for countries developing national systems. Findings underscore the need for a robust testing and sampling strategies, streamlined sample referral, and integrated data management with metadata linkage and data quality crucial for impactful epidemiological analysis. We recommend developing national genomic surveillance strategies to guide sustainable and integrated expansion of capacities built for COVID-19 and to optimize effective utilization of sequencing data for public health action.